Work-Family Conflict, Organizational-Based Self-Esteem and Pay Satisfaction as Predictors of Intention to Quit Among Bankers in Nigeria - Iloke, Stephen Ebuka (Practicum Psychologia, 2024)
This study investigated work-family conflict, organizational-based self-esteem and pay satisfaction as predictors of intention to quit among bankers. Five hundred and sixteen bankers of southeastern Nigeria participated in the study. They comprised 393 females and 123 males. Their age ranged from 21 to 53 years, with mean age of 33.3 years and standard deviation of 9.6. Five-item intention to quit scale developed by Faloye (2014), 10-item work-family conflict scale developed by Netemeyer, Boles and Mcmurrian (1996), 12-item organizational-based self-esteem scale developed by Pierce, Gardner, Cummings & Dunham, (1989) and pay satisfaction questionnaire developed by Heneman and Schwab (1985) and as validated by Joe-Akunne and Ezeh (2019) were the research instruments used for the study. The study adopted cross-sectional research design. Consequently, hierarchical linear regression statistic was employed for the analysis of data. The results showed that work-family conflict positively and significantly correlated with intention to quit at r = .75, p < .01. On the contrary, organizational-based self-esteem and pay satisfaction were negatively and significantly correlated with intention to quit at r = -.15, p< .01; -.19, p< .01, respectively. The interaction between work-family conflict, organizational-based self-esteem, pay satisfaction, and intention to quit accounted for significantly more variance than just sociodemographic factors; R2 change = .62 at p< .01, and this change in R2was significant at F(3,509) = 142.42, p <. 01. It was recommended that employees understand that in as much as mankind exists, one must work to earn a living. In working to earn a living, conflict of some sort may be encountered between their work roles and family expectations. Employees have to live with this in good fate.